2018
DOI: 10.1007/s40620-018-0542-y
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplantation in patients with previous renal cancer: a critical appraisal of current evidence and guidelines

Abstract: Due to the increasing occurrence of renal cell carcinoma (RCC) in the general population and the high prevalence of chronic kidney disease among cancer patients, many people with a previous RCC are considered as potential candidates for renal transplantation. They should accordingly be evaluated to assess their life expectancy and the risk that the chronic immunosuppressive therapy needed after grafting might impair their long-term outcome.Current guidelines on listing patients for renal transplantation sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Therefore, KT candidates are screened for malignant tumors, and RCC is detected occasionally. Previous studies have recommended a waiting time of 2 to 5 years for KT in patients with ESRD with RCC but suggested no delay in patients with asymptomatic and small RCC [1215]. However, this recommendation was based mainly on overseas studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, KT candidates are screened for malignant tumors, and RCC is detected occasionally. Previous studies have recommended a waiting time of 2 to 5 years for KT in patients with ESRD with RCC but suggested no delay in patients with asymptomatic and small RCC [1215]. However, this recommendation was based mainly on overseas studies.…”
Section: Discussionmentioning
confidence: 99%
“…As kidney transplant (KT) recipients typically receive immunosuppressive therapy, cancer recurrence after KT is a clinically important issue. Therefore, there are guidelines regarding waiting time for KT in patients with ESRD and RCC [12]. Previous studies have suggested a waiting period of 2 to 5 years before KT in patients with symptomatic RCC and no delay in patients with incidental early-stage RCC [1315], which is sometimes diagnosed during the pre-KT workup.…”
Section: Introductionmentioning
confidence: 99%
“…A higher percentage of deaths was observed in the cancer group in the total sample, a likely reflection of the higher age in this group as this difference was not observed in the age matched sample. A significantly lesser proportion of patients in the cancer group received a kidney transplant, which may indicate a mindful risk-based approach in the transplant work-up [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, pre-TM is considered a relative contraindication because pre-TM itself is a risk factor for cancer recurrence and renal cancer recurs in up to 21% of cases ( 14 ) as well because immunosuppressive therapies throughout a recipient’s life contribute to the risk of cancer onset and recurrence ( 15 ). Although some guidelines on KTX for RCC-induced ESRD have been reported, few studies have reported the exact number of RCC-induced ESRD patients who successfully received transplantation ( 16 ).…”
Section: Introductionmentioning
confidence: 99%